Promoting Responsible Generative AI Integration through Educational Leadership in Public Schools - Tanate, Aldin (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explores how educational leadership influences the responsible utilization of Generative Artificial Intelligence (GenAI) in public schools, emphasizing the critical role of leaders in guiding ethical, effective, and pedagogically sound adoption of AI tools across administrative and instructional domains. As AI becomes increasingly integrated into educational systems, leaders are responsible for shaping teacher engagement, promoting professional development, and supporting instructional practices, including lesson planning, assessment creation, and administrative workflow optimization. Using a descriptive-exploratory qualitative design, the study conducted semi-structured interviews with school leaders, including principals and district supervisors, and analyzed relevant policy documents to capture leadership strategies, decision-making processes, and ethical considerations in AI integration. Findings indicate that leadership practices, such as establishing clear AI policies, providing structured and continuous professional development, modeling ethical AI use, and fostering participatory decision-making, significantly enhance teacher confidence, motivation, and pedagogical competence. Leaders who actively support AI integration enable teachers to use GenAI tools responsibly, improving instructional efficiency, creativity, and innovation while mitigating risks of over-reliance on automated outputs or misalignment with curriculum objectives. The study concludes that responsible and sustainable AI integration depends on effective educational leadership that combines policy guidance, capacity-building initiatives, and ethical oversight. Recommendations include implementing formal AI guidelines, ongoing professional development programs, collaborative mentoring, monitoring systems, and reflective practices to ensure equitable, ethical, and impactful AI use. By leveraging these leadership strategies, public schools can maximize the educational benefits of GenAI, maintain teacher agency, enhance instructional quality, and uphold ethical standards, ultimately fostering an innovative, technology-enhanced learning environment that is safe, inclusive, and effective for both educators and learners.